Digital-Based and Telerehabilitation Interventions in Orthopaedic Postoperative Recovery: Literature Review - Albertina Dete Tabik; Asroful Hulam Zamroni; Aqmarina Abidah; I Made Dwi Budhiasa Ari Serengga; Johanes Eban B. Dorman; Kiki Fajar Nurhidayah; Lisa Isdaryanti; Rizki Nur Azhadin; Nursalam Nursalam; Tintin Sukartini; Akhmad Ja'far; Hendra Kurnia Rakhma (GLOBAL HEALTH SCIENCE GROUP, 2026)
Orthopedic surgery aims to treat musculoskeletal disorders; however, postoperative recovery often presents functional limitations. Digital interventions and telerehabilitation are increasingly being applied in nursing, although evidence of their effectiveness remains limited. This systematic review evaluated the effectiveness of these technologies in supporting postoperative orthopedic recovery and identified their contributions to evidence-based nursing practice. A systematic review following the PRISMA guidelines was conducted using Scopus, PubMed, Web of Science, ScienceDirect, and SAGE databases. Randomized controlled trials and quasi-experimental studies published between 2015 and 2025 involving adult postoperative orthopedic patients were included. The interventions were compared with conventional rehabilitation. Six outcome domains were evaluated: physical function, quality of life, pain, psychosocial aspects, self-efficacy, patient compliance and satisfaction. A total of 1,508 articles were identified, of which 16 studies met the inclusion criteria. Digital-based interventions and telerehabilitation consistently improved physical function (e.g., Timed Up and Go, Functional Independence Measure), increased quality of life (EQ-5D, SF-36), and reduced postoperative pain more rapidly than conventional rehabilitation did. Improvements were also observed in anxiety, depression, self-efficacy, health literacy, patient satisfaction, and adherence to the rehabilitation program. Digital and telerehabilitation interventions effectively support orthopedic postoperative recovery, positively affecting physical, psychosocial, and behavioral outcomes. A multimodal model integrating education, exercise, occupational therapy, and psychosocial support based on self-efficacy and biopsychosocial approaches yielded optimal results. Integration into surgical nursing practice is recommended, with attention to technological infrastructure and clinician training.